Testis-specific actin-like 7A (ACTL7A) is an indispensable protein for subacrosomal-associated F-actin formation, acrosomal anchoring, and male fertility. (3rd February 2023) - Ferrer, P; Upadhyay, S; Ikawa, M; Clement, T M
Abstract: Formation of the acrosome during spermiogenesis is an essential process for creating fertilization-competent sperm. Of the numerous aspects required for acrosome biogenesis, adherence of the acrosomal outer membrane to the nuclear surface is mediated by the subacrosomal perinuclear theca. However, the cellular dynamics and congruent functions pertaining to these acrosomal anchoring factors are not well understood despite many of them being implicated as potential causes for human male infertility. Actin-like 7A (ACTL7A) is one such factor for which deleterious polymorphisms have recently been shown to cause human male infertility. It is thought that acrosomal attachment is coordinated by cytoskeletal associations between the acrosome and nucleus via the acroplaxome. To further illuminate the mechanistic underpinnings of ACTL7A for essential acrosome associations, in this study, we investigated its dynamic localization in the developing germline, molecular associations with other cytoskeletal components, and the cellular consequences of ablation. Our intracellular localization data show ACTL7A to be dynamically present within the nucleus and subacrosomal space and later associated with postacrosomal regions of developing spermatids. Through the generation of an Actl7a knock-out mouse model, we consistently observed disruption of acrosomal biogenesis with abnormal migration of the acrosomal granule and peeling acrosomes during spermatid elongation. Significantly, we found a complete loss of subacrosomal filamentous actin (F-actin) structures in knock-out spermatids suggesting a regulatory role for subacrosomal F-actin. Considering our reported data together with existing literature, we propose a mechanistic model explaining the essential role of ACTL7A for acroplaxome-associated F-actin, acrosomal attachment integrity, and male fertility.